The influence of negative stereotypes in science fiction and fantasy on public perceptions of artificial intelligence: a systematic review - Bo, Duan; Ma’rof, Aini Azeqa; Zaremohzzabieh, Zeinab (Redfame Publishing, 2024)
This systematic literature review (SLR) explores the impact of negative stereotypes in science fiction and fantasy on public attitudes towards artificial intelligence (AI). By analyzing 9 studies published between 2011 and 2023, this review identifies key themes related to fear, distrust, ethical concerns, and the influence of media portrayals on the acceptance and adoption of AI technologies. The findings indicate that negative portrayals in these genres significantly increase fear and anxiety towards AI, leading to heightened skepticism and ethical concerns. Moreover, these negative stereotypes hinder the acceptance of AI in various fields, particularly affecting younger demographics more profoundly. This review highlights the need for more balanced and diverse media portrayals of AI to mitigate negative attitudes and promote a more nuanced understanding of AI technologies, particularly in light of its increasing role in various sectors.